HADIS PENDIDIKAN ETIKA SOSIAL SERTA URGENSINYA TERHADAP MASYARAKAT - M. Kharis Fadillah (SHAHIH (Jurnal Ilmu Kewahyuan), 2022)
The problem of social ethics is very crucial, especially from the point of view of a pluralistic or heterogeneous society, this is very likely for social problems to occur. However, there are several things that have been done in the direction of improving social ethics for a pluralistic society, one of the ways is by carrying out education on the Hadiths about social ethics in the community.